Dealing With Incomplete Household Panel Data in Inequality Research - Joachim R. Frick; Markus M. Grabka; Olaf Groh-Samberg (Sociological Methods & Research, 2012)
In trying to capture complete within-household heterogeneity, household panel surveys typically try to interview all adult household members. Following from this, such surveys tend to suffer from partial unit nonresponse (PUNR), that is, the nonresponse of at least one member of an otherwise participating household, most likely yielding an underestimation of aggregate household income. Using data from the German Socio-Economic Panel (SOEP), the authors evaluate four different strategies to deal with this phenomenon: (a) ignorance, that is, assuming the missing individual's income to be zero; (b) adjustment of the equivalence scale to account for differences in household size and composition; (c) elimination of all households observed to suffer PUNR and reweighting of households observed to be at risk of but not affected by PUNR; and (d) longitudinal imputation of the missing income components. The aim of this article is to show how the choice of technique affects substantive results in inequality research. The authors find indications of substantial bias on income inequality and poverty as well as on income mobility.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; household panel surveys; partial unit nonresponse; inequality; mobility; imputation; SOEP; Statistische Methode; Panel; Einkommensverteilung; Mobilität